Development of Silver Nanoparticles of Balanites Aegyptiaca Plant Extract for the Effective Treatment of Fungal Diseases - Prabhaker, Nishant; Patel, Ajay; Kumar Jain, Umesh (Asian Journal of Pharmaceutical Research and Development, 2024)
Invasive fungal diseases (IFDs) are an increasingly common complication in critically ill patients in world and are frequently fatal. Because of changes in treatment strategies and the increased use of antifungal prophylaxis, the epidemiology of IFDs has changed substantially in recent years and infections due to Candida species are no longer the majority in many institutions. Invasive candidiasis (IC) can affect individuals with various underlying diseases hospitalized in different parts of hospitals. In recent decades, IC has caused 27–55% mortality in general population. Treatment of invasive fungal infections is challenging as the number of existing antifungals is limited and more problems include: toxicity, drug interactions, and drug resistance. Hence there is need to acknowledge alternative remedies for fungal treatment. Plants are not only important to the millions of people to whom traditional medicine serves as the only opportunity for health care and to those who use plants for various purposes in their daily lives, but also as a source of new pharmaceuticals. The use of silver nanoparticles (AgNPs) against various pathogens is now being well recognized in the agriculture and health sector.